Wild animals endoparasites (Nemathelminthes and Platyhelminthes) from the Manu Biosphere Reserve, Peru - Tantaleán, Manuel (2004)
During 2001, eight genera (three identified to species level) of endoparasites were collected from wild mammals and birds in Peru. These collections were part of a large survey along an elevational gradient (470 – 3780 m.) on the Southwestern border of the Manu Biosphere Reserve (Departments of Cusco and Madre de Dios). Parasites were field–fixed in 70% ethyl alcohol and transported to the laboratory, where nematodes were cleared and cestodes were stained using standard procedures. Identification of some specimens was impossible. Nonetheless, the material is of exceptional interest because it includes the first Peruvian records of some taxa. Our findings include: Rhopalias caballeroi Kifune and Uyema, 1982, Rhopalias sp. (probable n. sp.), Taenia pisiformis Bloch, 1780 (cysticercus), Mesocestoides sp. (tetratyridia), Aprocta sp., Evaginuris branicki Mc Clure, 1932, Haematospiculum sp., Protospirura sp., Diplotriaena sp., Thelazia sp. 1, Thelazia sp. 2, Thelazia sp. 3 and Subulura sp.